Study of complex formation of Cs+, ZrO2+, Sm3+, Eu3+ ions with histidine in aqueous solutions - Amerkhanova, Sh.K.; Golovanova, O.A.; Belgibaeva, D.S.; Uali, A.S.; Abdiken, F.S. (KSU Publ., 2015)
Complexation process of Cs+, ZrO2+, Sm3+, Eu3+ ions with histidine in aqueous solutions were studied using pH-titration method in the temperature range 298–318 K and ionic strength from 0.1 to 1. The stability constants of complex formation and thermodynamic parameters of complex formation (ΔH, ΔG, ΔS) were calculated on the basis of the experimental data.
Сулы ерітіндідегі металл иондары Cs+, ZrO2+, Sm3+, Eu3+ мен гистидин арасындағы кешен түзілуін зерттеу
Исследование комплексообразования ионов Cs+, ZrO2+, Sm3+, Eu3+ с гистидином в водных растворах
Keywords: histidine; metal ions; thermodynamics; enthalpy; free Gibbs energy; entropy